Sulfate pollution: evidence for electrochemical production of persulfate by oxidizing sulfate released by the surfactant sodium dodecyl sulfate - de F. Araújo, Karla C.; de P. Barreto, Jéssica P.; Cardozo, Jussara C.; dos Santos, Elisama Vieira; de Araújo, Danyelle M.; Martínez-Huitle, Carlos A. [UNESP] (Springer Nature, 2018)
There is increasing concern about contamination by surfactants that are used to extract organic pollutants during remediation of polluted soils and aquifers. For instance, the surfactant sodium dodecyl sulfate may produce sulfate, which is a pollutant at high concentrations. Reports suggest that when remediation involves sodium dodecyl sulfate and electrochemical treatments, SO4 2− ions could be produced then oxidized to persulfate (S2O8 2−). However, there is few knowledge on the mechanism of electrochemical production of sulfate and persulfate. Here, we tested for first time the electrochemical production of persulfate from sulfate released by oxidation of sodium dodecyl sulfate, using anodic oxidation with boron-doped diamond. Results show a high efficiency of persulfate production, reaching 2.5 μM, when 500 mg/L of surfactant in 0.05 mol/L of Na2SO4 was electrolyzed at 60 mA cm−2, by comparison with only 0.7 μM of persulfate without surfactant in solution. This efficiency is explained by electrogeneration of hydroxyl radicals and persulfate. Results also show that 97% of the surfactant is transformed by fragmentation and oxidation, as revealed by particle size measurements.
Keywords: Diamond electrode; Persulfate; Sodium dodecyl sulfate; Sulfate release; Surfactant